The Science of evaluation : a realist manifesto - Pawson, Ray (Los Angeles, California : Sage, 2013)
Evaluation researchers are tasked with providing the evidence to guide programme building and to assess its outcomes. As such they labour under the highest expectations to which they have responded with a huge portfolio of research techniques and schemes to establish standards for evaluative inquiry and to accredit evaluation practitioners. A big question remains : has this monumental effort produced a progressive, cumulative and authoritative body of knowledge that we might think of as evaluation science? This is the question addressed by Ray Pawson in this book.
Part 1 : Precursors and principles -- Part 2 : The Challenge of complexity : Drowning or waving? -- Part 3 : Towards evaluation science
Includes bibliographical references and index.
Keywords: EVALUATION RESEARCH (SOCIAL ACTION PROGRAMS)